Transcranial Direct Current Stimulation at 4 mA Induces Greater Leg Muscle Fatigability in Women Compared to Men - Craig D. Workman; Alexandra C. Fietsam; Thorsten Rudroff (Brain Sciences, 2020)
Transcranial direct current stimulation (tDCS) has previously shown different cortical excitability and neuropsychological effects between women and men. However, the sex-specific effects of tDCS on leg muscle fatigability has not been investigated. The purpose of this study was to determine the effects of a single session of 2 mA and 4 mA primary motor cortex tDCS on leg muscle fatigability in healthy young men and women in a crossover design. Twenty participants (women = 10) completed isokinetic fatigue testing (40 maximal reps, 120°/s) of the knee extensors and flexors in conjunction with sham, 2 mA, and 4 mA tDCS in a double-blind, randomized design. The fatigue index from each condition was calculated. Women had significantly greater knee extensor fatigability in the 4 mA condition compared to men (57.8 ± 6.8% versus 44.1 ± 18.4%; p = 0.041, d = 0.99). This study provides additional evidence that responses to tDCS may be sex-specific and highlights the necessity of accounting and powering for sex differences in future investigations.